Phase 1/2a study of the malaria vaccine candidate apical membrane antigen-1 (AMA-1) administered in adjuvant system AS01B or AS02A. - Michele D Spring (PLoS ONE, 2009)
This Phase 1/2a study evaluated the safety, immunogenicity, and efficacy of an experimental malaria vaccine comprised of the recombinant Plasmodium falciparum protein apical membrane antigen-1 (AMA-1) representing the 3D7 allele formulated with either the AS01B or AS02A Adjuvant Systems.After a preliminary safety evaluation of low dose AMA-1/AS01B (10 microg/0.5 mL) in 5 adults, 30 malaria-naïve adults were randomly allocated to receive full dose (50 microg/0.5 mL) of AMA-1/AS01B (n = 15) or AMA-1/AS02A (n = 15), followed by a malaria challenge. All vaccinations were administered intramuscularly on a 0-, 1-, 2-month schedule. All volunteers experienced transient injection site erythema, swelling and pain. Two weeks post-third vaccination, anti-AMA-1 Geometric Mean Antibody Concentrations (GMCs) with 95% Confidence Intervals (CIs) were high: low dose AMA-1/AS01B 196 microg/mL (103-371 microg/mL), full dose AMA-1/AS01B 279 microg/mL (210-369 microg/mL) and full dose AMA-1/AS02A 216 microg/mL (169-276 microg/mL) with no significant difference among the 3 groups. The three vaccine formulations elicited equivalent functional antibody responses, as measured by growth inhibition assay (GIA), against homologous but not against heterologous (FVO) parasites as well as demonstrable interferon-gamma (IFN-gamma) responses. To assess efficacy, volunteers were challenged with P. falciparum-infected mosquitoes, and all became parasitemic, with no significant difference in the prepatent period by either light microscopy or quantitative polymerase chain reaction (qPCR). However, a small but significant reduction of parasitemia in the AMA-1/AS02A group was seen with a statistical model employing qPCR measurements.All three vaccine formulations were found to be safe and highly immunogenic. These immune responses did not translate into significant vaccine efficacy in malaria-naïve adults employing a primary sporozoite challenge model, but encouragingly, estimation of parasite growth rates from qPCR data may suggest a partial biological effect of the vaccine. Further evaluation of the immunogenicity and efficacy of the AMA-1/AS02A formulation is ongoing in a malaria-experienced pediatric population in Mali.www.clinicaltrials.gov NCT00385047.